Viral complexes in the Allium cepa L.- Frankliniella occidentalis P. interaction by DAS-ELISA in Baja California, Mexico - Valle-Gough, Raúl Enrique; Samaniego-Gámez, Blancka Yesenia; Cervantes-Díaz, Lourdes; Samaniego-Gámez, Samuel Uriel; Garruña-Hernández, René; Núñez-Ramírez, Fidel; Ruiz-Sánchez, Esaú; Torres-Bojórquez, Ariana Isabel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The onion (Allium cepa L.) is one of the main horticultural crops produced in Baja California, Mexico. In this crop, it has been observed presumptive viral symptoms, which are able to cause losses in yield and quality. Therefore, the objective of this study was to detect the associated virus in onion in high producing culture zones in Baja California. Plant material samples (symptomatic and asymptomatic) and trips insects were collected from commercial farming or areas. Commercial anti-serum were used for the detection of Iris yellow spot virus (IYSV), Tomato spot wilt virus (TSWV), Leek yellow spot virus (LYSV), Onion yellow dwarf virus (OYDV) and Garlic common latent virus (GarCLV). Seven indicator plants species were mechanically inoculated with onion sap (symptomatic and asymptomatic). The results showed the presence of IYSV, TSWV, OYDV and GarCLV in symptomatic onion plants. The plant samples showed a 77 % of incidence in the form of viral complexes and in a 23 % only the presence of LYSV was detected. The trips identified as Frankiniella occidentalis P. harbored IYSV, TSWV, LYSV, OYDV and GarCLV in the form of complexes in La Trinidad and San Quintin. The indicator plants did not show sympotoms of virosis. It is evident that F. occidentalis P. is responsible for the transmision of the analyzed viruses in this study in cultured onions. There are not previous reports for the detection of Orthotospovirus, Potyvirus and Carlavirus in Baja California onions.